Managing Roles in Entrepreneurial Organisation: Array - Durowoju, Stella Toyosi; Tijani, Abideen Adekunle (Acta Universitatis Danubius. Œconomica, 2021)
The success of an entrepreneurial organisation towards meeting its objectives is largely dependent on the effective management of roles. An effective development and survival is attainable in entrepreneurial organisations since originators have the compassion to give their best for achieving the sustainability of the organisations through hard work and commitment. Entrepreneurs are generally thought to be abnormal people because they are unique and creative in their thoughts and ability to change an old way of doing things to more acceptable modern and global standard. This study used secondary data from extant literatures in international and local academic journal articles, textbooks and other useful articles on the web sites. The inability to get adequate responses from entrepreneurs is responsible for desk research due to the COVID-19 pandemic in Nigeria. Also, entrepreneurial organisations partially closed their businesses and this necessitated the use of secondary data. The study adopted two role models: Managerial Roles proposed by Henry Mintzberg and the Founder’s Multiple Roles Model by Peter Wilson and Sue Bates. The study concluded that roles that need to be implemented by the founders and their managers must be articulately carried out in entrepreneurial organisations in order to achieve stated objectives such as corporate survival. Furthermore, the study recommended that investment in training and development of workers should be put into consideration to enable them cope and adjust to assigned duties and functions that is accompanied by technological innovations towards corporate survival.